2021
DOI: 10.3390/cancers13246338
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Molecular Prognostic Classifier for Intermediate/High-Risk Clear Cell Renal Cell Carcinoma

Abstract: The probability of tumor progression in intermediate/high-risk clear cell renal cell carcinoma (ccRCC) is highly variable, underlining the lack of predictive accuracy of the current clinicopathological factors. To develop an accurate prognostic classifier for these patients, we analyzed global gene expression patterns in 13 tissue samples from progressive and non-progressive ccRCC using Illumina Hi-seq 4000. Expression levels of 22 selected differentially expressed genes (DEG) were assessed by nCounter analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…Another study illustrated that HS6ST2 was upregulated in NSCLC 22 and promoted cell development in NSCLC 23 . Our findings in renal clear cell cancer contradict those of earlier studies 17 , which showed that HS6ST2 is a potential prognostic biomarker and that inhibition of HS6ST2 causes decreased migration and invasion of RCC cells 18 . This inconsistency is likely attributable to the fact that earlier studies placed a greater emphasis on RCC cell lines with high metastatic ability.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another study illustrated that HS6ST2 was upregulated in NSCLC 22 and promoted cell development in NSCLC 23 . Our findings in renal clear cell cancer contradict those of earlier studies 17 , which showed that HS6ST2 is a potential prognostic biomarker and that inhibition of HS6ST2 causes decreased migration and invasion of RCC cells 18 . This inconsistency is likely attributable to the fact that earlier studies placed a greater emphasis on RCC cell lines with high metastatic ability.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study illustrated that HS6ST2 was highly expressed in papillary thyroid cancer, thyroid cancer, and high-grade cartilage tumor tissues 12 , though it was expressed at low levels in glioma tissues 13 , and HS6ST2 was also found to promote the development of thyroid cancer 14 , 15 . HS6ST2 expression was found to be negatively related to OS and was an independent prognostic factor for clear cell renal cell carcinoma patient outcomes 16 , 17 . Furthermore, HS6ST2 can be downregulated by miR-145-5p, limiting the development of renal cell carcinoma (RCC) cells 18 .…”
Section: Introductionmentioning
confidence: 94%
“…Its overexpression promotes cell viability, proliferation and invasion, it is involved in the PI3K/AKT pathway [ 36 ] and is part of an immune prognostic signature for colon and rectal cancer [ 35 ]. HS6ST2 (heparan sulfate D-glucosaminyl 6- O -sulfotransferase-2) is a glycolysis-related gene and has also been associated with poor disease outcomes in numerous malignancies [ 10 , 37 ]. Interestingly, our group previously validated this gene as an independent prognosis biomarker in intermediate/high-risk ccRCC and found it to be associated with angiogenesis, epithelia–mesenchymal transition (EMT), and indirectly related to the PD-1, PDL-1 cancer immunotherapy pathway [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…HS6ST2 (heparan sulfate D-glucosaminyl 6- O -sulfotransferase-2) is a glycolysis-related gene and has also been associated with poor disease outcomes in numerous malignancies [ 10 , 37 ]. Interestingly, our group previously validated this gene as an independent prognosis biomarker in intermediate/high-risk ccRCC and found it to be associated with angiogenesis, epithelia–mesenchymal transition (EMT), and indirectly related to the PD-1, PDL-1 cancer immunotherapy pathway [ 37 , 38 , 39 ]. MIA2 (melanoma inhibitory activity 2) has been found in several malignancies and can act as a tumor suppressor [ 40 ] or as a proto-oncogene depending on the receptor-related signaling differences [ 41 ].…”
Section: Discussionmentioning
confidence: 99%